De inimigo público a herói nacional : representações da morte de Carlos Marighella - Soares, Wagner dos Santos (2012)
This work analyzes the different memories of Carlos Marighella, a communist revolutionary. He was targeted because his biography shows one of the leaders of the revolutionary left-wing political organizations, which had a political career that has generated great controversy related to the period of military dictatorship.Both, the need for an official version of his death and the action of a press tied to the military dictatorship helped, along the dictatorship, Marighella be represented as a dangerous terrorist and an enemy of the Brazilian nation. This research incorporates the process of formulating this official memory on it and that reached its peak with the recognition of state responsibility on his death. This study observed the existence of recent changes in the social representations about the death of Mariguella that tend to characterize him as a hero. This study incorporates these changes as expressions of conflicts between political agents of the right and left who seek to spread opposing and irreconcilable versions of the death of Mariguella.